Patenteamento em biotecnologias: A experiência chinesa - Graziela Ferrero Zucoloto (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– This paper aims to mapping the biotechnological regulatory aspects in China. It presents the historical evolution of biotechnologies in the country, focusing on the public support to the area. It discusses the main changes on Chinese Patent Law and details the patentable subject on biotechnologies, comparing them to selected countries. It presents a statistical analysis of granted patents on USPTO, characterizing them by owners, inventors and international codes of patents related to biotechnologies. Based on this discussion, it presents the final conclusions.
Keywords: O34; 330; legislation; patents; biotechnology; China